Lumen Loading : The effects of beating process on tensile index - Ramly, Rosazley; Zakaria, Sarani (Penerbit Universiti Sains Malaysia, 2004)
Lumen-loaded technology has been studied for many years especially by researchers in Pulp and Paper Research Institute of Canada (PAPRICAN) such as Green (1982, 1985), Middleton and Scallan (1985, 1989, 1991) and Van de Van (1994). In 1992, Rioux et. al and Marchessault have proved the suitability of magnetic particles such Fe2O3 and Fe3O4 to use in lumen-loaded process. This study relates to the effects of beating process on tensile index.